2021
DOI: 10.1063/5.0062579
|View full text |Cite
|
Sign up to set email alerts
|

Wear trends of the 12.5 kW HERMeS Hall thruster

Abstract: This work presents the results of over 6500 h of wear testing completed during the maturation of the NASA 12.5 kW Hall Effect Rocket with Magnetic Shielding. Erosion of the thruster front pole covers was found to be the primary life-limiting mechanism and exhibits strong dependencies on thruster operating condition and material properties. Specifically, average pole cover erosion rates increased by 76% as discharge voltage decreased from 600 to 300 V and 42%–96% as the magnetic field increased from 0.75 to 1.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In long duration tests of a high power Hall thruster, Frieman showed that high density graphite pole covers that were initially polished developed μm-scale roughness after about 5-6 μm were removed. 2 In this case, the ions are believed to have much larger global incidence angles. In contrast, pyrolytic graphite appears to remain unchanged or get smoother due to exposure.…”
Section: Surface Roughness Effectsmentioning
confidence: 99%
See 3 more Smart Citations
“…In long duration tests of a high power Hall thruster, Frieman showed that high density graphite pole covers that were initially polished developed μm-scale roughness after about 5-6 μm were removed. 2 In this case, the ions are believed to have much larger global incidence angles. In contrast, pyrolytic graphite appears to remain unchanged or get smoother due to exposure.…”
Section: Surface Roughness Effectsmentioning
confidence: 99%
“…Graphite is used in many electric propulsion applications because of its thermal and mechanical characteristics and its sputter resistance. For example, high density graphite is used for sputter-resistant keeper electrodes in ion and Hall thrusters 1,2 and as front pole covers in magnetically shielded Hall thrusters to protect more sensitive magnetic components. 2,3 Graphite and carbon-carbon composite grids are used in ion thrusters to extend engine life.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…E.g. deriving factors which foster differences between in-space and facility performance [20], minimizing erosion rates [21][22][23][24], studying anomalous electron diffusion, microturbulence, and axial ion-ion streaming instabilities [25][26][27][28][29], etc. The resolution of this phenomena is particularly important in the improvement of numerical simulations-seeking to partially supplant timely, expensive test and qualification campaigns.…”
Section: Introductionmentioning
confidence: 99%